2020
DOI: 10.1002/jcla.23628
|View full text |Cite
|
Sign up to set email alerts
|

VE1 immunohistochemistry is an adjunct tool for detection of BRAFV600E mutation: Validation in thyroid cancer patients

Abstract: Papillary thyroid carcinoma (PTC) is the most common endocrine malignancy among other endocrine tumors, and BRAFV600E is a frequent genetic mutation occurring in the disease. Although different molecular techniques, most importantly sequencing has been widely recognized as a gold standard but molecular diagnosis remains an expensive, laborious, and time‐intensive process. Recently, immunohistochemistry (IHC) with anti‐BRAF V600E (VE1) antibody has increased practical utility and implemented clinically for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…This study shows that the female gender is more predominant in PTC than males. This finding is consistent with Rashid et al , who demonstrated a high female prevalence compared to males [ 19 ], and more studies agreed with this finding [ 24 , 25 ]. Another study demonstrated no differences between females and males [ 26 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study shows that the female gender is more predominant in PTC than males. This finding is consistent with Rashid et al , who demonstrated a high female prevalence compared to males [ 19 ], and more studies agreed with this finding [ 24 , 25 ]. Another study demonstrated no differences between females and males [ 26 ].…”
Section: Discussionsupporting
confidence: 92%
“…The BRAF is the most prevalent mutation in thyroid cancer, which occurs in more than 50% of papillary thyroid cancers (PTCs) and approximately 45% of anaplastic thyroid cancer [ 18 ]. Asian populations have a higher BRAF mutation rate than Western countries [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Rashid et al ( 51 ) previously reported an IHC analysis method for PTC tissues using VE1 antibody, where a rate of concordance of 98.6% was found between IHC and sequencing-based mutation detection in 72 patients with PTC. In addition, the detection rate of BRAF mutation was higher in IHC analysis compared with Sanger sequencing.…”
Section: Techniquesmentioning
confidence: 99%
“…Genetic methods like high resolution melting (HRM) analysis, pyrosequencing, amplification refractory mutation system (ARMS) or allelespecific PCR, and next generation sequencing (NGS) are other testing methods. 12 Interestingly, immunohistochemistry (IHC), a widely available low-cost technique is a highly sensitive and specific detection method for BRAFV600E in melanoma and thyroid cancer 13,14 which makes IHC a very useful adjunctive test for BRAFV600E in ameloblastoma.…”
Section: Introductionmentioning
confidence: 99%